Introduction to Psychology - Shashi Jain; JAIN (Shashi) (Ludhiana Kalyani Publishers, 2021)
For undergraduate students of Indian Universities. The book covers the syllabii but more than that it covers the fundamental aspects like methods of Psychology, Variables Biological foundations of Psychology, Sensory & Perceptual Processes, Laearning & Memory, Motivation & emotion, intelligence, Personality, thinking and Stress & its management
Keywords: Methods of Psychology; Heredity and Environment; Attention; Perception; Stress and its Management